Hospitalization for ambulatory care sensitive conditions: What conditions make inter-country comparisons possible? - João Victor Muniz Rocha; Rui Santana; Juan E. Tello (Elsevier, 2021)
Hospitalizations for ambulatory care sensitive conditions have been extensively used in health services research to assess access, quality and performance of primary health care. Inter-country comparisons can assist policy-makers in pursuing better health outcomes by contrasting policy design, implementation and evaluation. The objective of this study is to identify the conceptual, methodological, contextual and policy dimensions and factors that need to be accounted for when comparing these types of hospitalizations across countries. A conceptual framework for inter-country comparisons was drawn based on a review of 18 studies with inter-country comparison of ambulatory care sensitive conditions hospitalizations. The dimensions include methodological choices; population's demographic, epidemiologic and socio-economic profiles and features of the health services and system. Main factors include access and quality of primary health care, availability of health workforce and health facilities, health interventions and inequalities. The proposed framework can assist in designing studies and interpreting findings of inter-country comparisons of ambulatory care sensitive conditions hospitalizations, accelerating learning and progress towards universal health coverage.